2011
DOI: 10.3390/ani1040396
|View full text |Cite
|
Sign up to set email alerts
|

Signs Observed Among Animal Species Infected with Raccoon Rabies Variant Virus, Massachusetts, USA, 1992–2010

Abstract: Simple SummaryWe analyzed signs occurring among domestic and wild terrestrial animal species with raccoon rabies variant virus in Massachusetts, 1992–2010. While aggression is a useful predictor of rabies among wild animals, combinations of other signs such as ataxia, disorientation, and salivation are useful predictors of rabies among domestic animals.AbstractWe analyzed signs occurring among domestic and wild terrestrial animal species infected with raccoon rabies variant virus (RRV) in Massachusetts, 1992–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…() reported that the biting behaviour of rabid dogs was highly variable, highlighting that a small number of individuals can disproportionately drive rabies transmission. However, recent studies (Tepsumethanon et al., ; Wang et al., ) have cast doubt on the relationship between aggression and rabies infection in pets (particularly cats and dogs).…”
Section: Rabiesmentioning
confidence: 99%
See 1 more Smart Citation
“…() reported that the biting behaviour of rabid dogs was highly variable, highlighting that a small number of individuals can disproportionately drive rabies transmission. However, recent studies (Tepsumethanon et al., ; Wang et al., ) have cast doubt on the relationship between aggression and rabies infection in pets (particularly cats and dogs).…”
Section: Rabiesmentioning
confidence: 99%
“…Other studies have continued to highlight the relationship between rabid wildlife and aggressive behaviour (Rosatte et al., ; Wang et al., ,b, ). However, only suspect rabid animals were included in these studies, and as such, aggressive behaviour of wild animals may be over reported compared with clinical signs of dumb rabies (i.e.…”
Section: Rabiesmentioning
confidence: 99%
“…Additionally, raccoons are known hosts for rabies and were recently shown to still be the primary host species for this disease in the USA ( 24 ), despite massive rabies bait vaccinations campaigns. Interestingly, as both rabies and CDV can present with neurological signs (including ataxia and disorientation) ( 25 ), it could be difficult to distinguish these diseases at first sight. A recent report additionally indicated that raccoons thought to be drunk from eating fermented crab apples were actually sick with distemper.…”
Section: Discussionmentioning
confidence: 99%